Cultural territorialization: The case of Grand Duchy of Lithuania - Tomas Kačerauskas (Creativity Studies, 2010)
The article deals with the dialectics of territorialization, deterritorialization and reterritorialization in the context of cultural regionalistics. The author shows how changing the roles between these modes of terra dynamics influences the becoming of culture interpreted as existential creation. Grand Duchy of Lithuania (GDL) has been used as the case for the development of these ideas in the paper. According to the author, we deal with the polyphonic process of territorialization while the physical aspect serves as a background for cultural deterritorialization and vice versa. The perspective of cultural regionalistics presupposes an existential approach (culture as existential creation), as well as border discourse, while border has been interpreted as cultural phenomenon to be cultivated by both an individual and the nation. The major thesis is the following: the very dynamism of life‐world's borders follows from human existential creativity, the source of which is being towards death. The minor thesis: a nation is alive as a terra for individual (re)birth while he (she) creates the future community by his (her) activity. The author presents two kinds of communication during territorialization: horizontal, which deals with realization of a utopia, and vertical, which deals with the myths of the nation's past. The change of roles between different aspects of human terra signifies not linear multi‐layered development of culture as a fight for creative space or existential territory. According to the author, reterritorialization presupposes a temporal aspect, which regards all three modes because of dialectics between them. Historical images have been used in our political terra and, vice versa, historical terrae have been understood in political perspective.